2020
DOI: 10.3390/bioengineering7040146
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bionics Assessment of Anorectal Mechanosensory Physiology

Abstract: Biomechatronics (bionics) is an applied science that creates interdisciplinary bonds between biology and engineering. The lower gastrointestinal (GI) tract is difficult to study but has gained interest in recent decades from a bionics point of view. Ingestible capsules that record physiological variables during GI transit have been developed and used for detailed analysis of colon transit and motility. Recently, a simulated stool named Fecobionics was developed. It has the consistency and shape of normal stool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…We found 24% reduction in symptoms, and 7 patients (58%) were considered responders. This is close to what have been reported by others, such as 53% ( 38 ) and 63% ( 39 ). It is better than that in another study ( 37 ) that by the way also showed no improvement in the QOL score.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found 24% reduction in symptoms, and 7 patients (58%) were considered responders. This is close to what have been reported by others, such as 53% ( 38 ) and 63% ( 39 ). It is better than that in another study ( 37 ) that by the way also showed no improvement in the QOL score.…”
Section: Discussionsupporting
confidence: 92%
“…However, large-scale studies are required to further assess subtype phenotypes and treatment effects. Future studies may take advantage of improved wireless devices that in addition can measure the anorectal angle and the bag shape (38)(39)(40)(41)(42). Future studies may also examine the efficacy of Fecobionics as a therapeutic tool for performing biofeedback treatment in FI patients.…”
Section: Pathophysiological Aspectsmentioning
confidence: 99%
“…The basic design of the previous Fecobionics prototype has been previously described (Chen et al, 2020; Gregersen, 2020; Gregersen, Sun, et al, 2021; Kassab et al, 2021; Sun et al, 2019). Previous versions recorded pressures only or did not have an integrated graphical user interface.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have been done on patients with FI including patients with low anterior resection syndrome (LARS) and CC including obstructed defecators (Chen et al, 2021b; Gregersen et al, 2020; Gregersen, Chen, et al, 2021). Furthermore, pilot studies have been done with an early stage integrated Fecobionics prototype in colon and anorectum (Gregersen, 2020; Gregersen, Sun, et al, 2021; Gregersen, Wang, et al, 2021; Kassab et al, 2021; Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation